2008
DOI: 10.1111/j.1532-950x.2007.00350.x
|View full text |Cite
|
Sign up to set email alerts
|

Pes Varus Correction in Dachshunds Using a Hybrid External Fixator

Abstract: Visual inspection of limb alignment during surgery resulted in good to excellent clinical outcomes; however, 91% of tibiae were under- or overcorrected (mean, 6 degrees; median, 5 degrees). Limb alignment should be based on evaluation of immediate postoperative TTJO measurements, not solely on intraoperative visual assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1
11

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(87 citation statements)
references
References 12 publications
3
72
1
11
Order By: Relevance
“…Medical histories were reviewed to attribute a lameness score to the cat at first presentation with the bent plate. Lameness was retrospectively graded as 0: no lameness; 1: subtle weightbearing lameness; 2: obvious weight-bearing lameness; 3: intermittent non-weight bearing lameness; 4: consistent non-weight bearing lameness (Radasch et al, 2008). Where a lameness score was not possible a description of the presenting signs was summarised.…”
Section: Plate Failurementioning
confidence: 99%
See 1 more Smart Citation
“…Medical histories were reviewed to attribute a lameness score to the cat at first presentation with the bent plate. Lameness was retrospectively graded as 0: no lameness; 1: subtle weightbearing lameness; 2: obvious weight-bearing lameness; 3: intermittent non-weight bearing lameness; 4: consistent non-weight bearing lameness (Radasch et al, 2008). Where a lameness score was not possible a description of the presenting signs was summarised.…”
Section: Plate Failurementioning
confidence: 99%
“…Tibial length was measured as the distance from the proximal tibial joint centre (PTJC) to the distal tibial joint centre (DTJC) on the craniocaudal (CC) radiograph (Radasch et al, 2008) (Figure 1). Fracture span was estimated by measuring the distance between the ends of major fracture segments and recorded as a percentage of tibial length (Figure 1).…”
Section: Fracture Reduction and Limb Alignmentmentioning
confidence: 99%
“…Stabilization of short juxta‐articular fracture or osteotomy segments may only allow placement of a single ring when applying a circular construct . and most hybrid constructs typically use only a single ring …”
Section: Discussionmentioning
confidence: 99%
“…Clinical circumstances influence appropriate implant selection of supplemental fixation elements when applying a circular or hybrid construct . Placement of a drop wire, rather than a supplemental half‐pin, would theoretically afford more optimal motion at the fracture or osteotomy gap when axial elasticity of the secured bone segments is considered beneficial to promote osseous union.…”
Section: Discussionmentioning
confidence: 99%
“…One dog developed lameness associated with drainage from the most proximal pin but this resolved after pin removal and antibiotic administration. It was reported that placement of 3 pins in the proximal segment in these dogs would have been technically challenging and could have compromised the adjacent soft tissues 15 . Typical type 1a ESF frames ideally have 3 or 4 pins in the proximal and distal segments 8,12 .…”
Section: Discussionmentioning
confidence: 99%